2004
DOI: 10.1016/j.jasms.2003.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Automated de novo sequencing of nucleic acids by liquid chromatography-tandem mass spectrometry

Abstract: We present the first global computer-aided sequencing algorithm for the de novo determination of short nucleic acid sequences. The method compares the fragment ion spectra generated by collision-induced dissociation of multiply charged oligodeoxynucleotide-ions to the m/z values predicted employing established fragmentation pathways from a known reference sequence. The closeness of matching between the measured spectrum and the predicted set of fragment ions is characterized by the fitness, which takes into ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Cation adduction can be reduced by sample preparation or through addition of chelators or organic bases to the mobile phase. The direct on-line combination of liquid Oberacher et al 16 found that collision energy had a major impact on the ability to interpret MS/MS spectra. The optimum collision energy has to be high enough to generate fragments covering the sequence as completely as possible by a-B and w ions, but low enough to suppress secondary and/or alternative fragmentation pathways.…”
Section: Rcm Letter To the Editormentioning
confidence: 99%
“…Cation adduction can be reduced by sample preparation or through addition of chelators or organic bases to the mobile phase. The direct on-line combination of liquid Oberacher et al 16 found that collision energy had a major impact on the ability to interpret MS/MS spectra. The optimum collision energy has to be high enough to generate fragments covering the sequence as completely as possible by a-B and w ions, but low enough to suppress secondary and/or alternative fragmentation pathways.…”
Section: Rcm Letter To the Editormentioning
confidence: 99%
“…Several groups including the Vouros research group have also been working on the development of data mining software of mass spectrometric data for nucleic acids for the last few years [90–95]. For example GenoMass software, based on the ‘reversed pseudo-combinatorial’ approach developed in the Vouros lab is a fast, automated, efficient, high-throughput data-mining algorithm for mass spectrometric analysis of nucleic acids [94,95].…”
Section: Mass Spectrometry In the Analysis Of Oligonucleotide Adductsmentioning
confidence: 99%
“…Rosenski and McCloskey have introduced a local search algorithm called "Simple Oligonucleotide Sequencer" (SOS) [38], which represents an efficient sequencing algorithm for the ab initio determination of unknown oligonucleotide sequences at approximately the 20-mer level and below. We have presented a global sequencing strategy [43]. Starting from a known nucleotide composition, all possible nucleic acid sequences and corresponding theoretical tandem mass spectra are generated and compared to the experimental spectrum.…”
Section: Sequencementioning
confidence: 99%